The story of the Monitor and the Merrimac - Stein, R. Conrad; Neely, Keith, 1943- (Chicago : Childrens Press, 1983)
An account of the naval duel fought in the Chesapeake Bay between the opposing ironclads of the North and the South.
13 15 26
Keywords: Monitor (Ironclad) -- Juvenile literature; Monitor (Ironclad).; Merrimack (Frigate).; Merrimack (Frigate) -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- History -- 1961-1865, Civil War; United States -- History -- Civil War, 1861-1865 -- Naval operations -- Juvenile literature